2016
DOI: 10.1016/s1875-5372(17)30038-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Property of Al-5Zn-2Mg Aluminum Alloy Welding Joints Used in High-speed Trains

Abstract: The fatigue property of Al-5Zn-2Mg aluminum alloy Metal-Inert Gas (MIG) welding joints used in high-speed trains was studied by a fatigue machine. Scanning electron microscopy (SEM) was used to observe the fatigue fracture and the surface damage. The results show that uniaxial ratcheting behavior occurs in the welding zone (WZ) when the stress is higher than 0.5σb; there are obvious plastic deformations in the WZ and a lot of slip bands on the surface, which reduce the fatigue life of the sample. The uniaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The post-processing treatments of notched samples noticeably affected the local ratcheting resistance of materials under remotely asymmetric loading cycles. Weiyuan et al [20] conducted fatigue tension-tension tests on aluminum Al-5Zn-2Mg samples post-welded by the process of MIG filler wire welding with an ER5356 welding electrode. They observed the progressive plastic strain mainly within the weld zone as loading cycles proceeded.…”
Section: Introductionmentioning
confidence: 99%
“…The post-processing treatments of notched samples noticeably affected the local ratcheting resistance of materials under remotely asymmetric loading cycles. Weiyuan et al [20] conducted fatigue tension-tension tests on aluminum Al-5Zn-2Mg samples post-welded by the process of MIG filler wire welding with an ER5356 welding electrode. They observed the progressive plastic strain mainly within the weld zone as loading cycles proceeded.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Huili [3] et al conducted metallographic, hardness, and tensile tests on the weld zone to verify the performance of YC2 titanium alloy after traditional welding. In 2009, Li Jinwei [4] et al studied the microstructure distribution characteristics of Ti60 alloy after electron beam welding. In 2012, E. Dalgaard [5] et al studied the properties of  titanium alloy after linear friction welding by changing the axial pressure during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Ni et al. [13] found that the fatigue fracture of Al–5Zn–2Mg aluminium alloy MIG joint occurred in the HAZ when the stress level was lower than 50% of joint tensile strength, otherwise it occurred in the fusion zone (FZ). Balasubramanian et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fatigue performance of MIG-welded aluminium alloy joint is the research focus. Ni et al [13] found that the fatigue fracture of Al-5Zn-2Mg aluminium alloy MIG joint occurred in the HAZ when the stress level was lower than 50% of joint tensile strength, otherwise it occurred in the fusion zone (FZ). Balasubramanian et al [14] investigated the influences of pulsed current welding and post-weld ageing treatment on fatigue crack growth behaviour of AA7075 aluminium alloy joints.…”
Section: Introductionmentioning
confidence: 99%